Concrete - Pictorial - Abstract Approaches to Mathematics Education: A Systematic Literature Review - Azzumar, Fuji; Juandi, Dadang (Universitas Sebelas Maret, 2023)
This research is a systematic literature review (SLR) research that focuses on the implementation of the CPA approach in mathematics education. This study aims to look at a more in-depth and comprehensive view of the implementation of the CPA approach in mathematics education in terms of the year of research and level of education. There were 20 research articles collected and analyzed based on predetermined inclusion and exclusion criteria. During the period 2018 to 2022 it was found that the implementation of the CPA approach to mathematics learning outcomes, students' mathematical abilities, students' affective abilities was mostly carried out at the elementary level. The implementation of the CPA approach at the junior high school level has been carried out, but it is still small. At the high school level, at least it was carried out, only 2 articles were found that used high school students as subjects. Overall the CPA approach improves students' learning outcomes in mathematics, mathematics ability, and students' affective abilities at every level of education.